2015
DOI: 10.5194/bg-12-1615-2015
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and discontinuous variation in ecosystem carbon stocks with elevation across a treeline ecotone

Abstract: Abstract. Treelines differentiate vastly contrasting ecosystems: open tundra from closed forest. Treeline advance has implications for the climate system due to the impact of the transition from tundra to forest ecosystem on carbon (C) storage and albedo. Treeline advance has been seen to increase above-ground C stocks as low vegetation is replaced with trees but decrease organic soil C stocks as old carbon is decomposed. However, studies comparing across the treeline typically do not account for elevational v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…K and Mg also decrease in soil Ah horizons, however not significantly (Table 3). In foliage, similar results were found for tree species Abies spectabilis and Sorbus microphylla (not illustrated) which both occur in the closed forest and sparsely as krummholz above treeline, however here not in tree form as defined by Körner Speed et al, 2015;Zimmermann et al, 2010), whereas soil N concentrations (Of, Ah) significantly decrease ( Figure 6). Thus, significantly increasing C/N ratios ( Figure 6, Table 3; cf.…”
Section: Hohnwaldsupporting
confidence: 79%
See 1 more Smart Citation
“…K and Mg also decrease in soil Ah horizons, however not significantly (Table 3). In foliage, similar results were found for tree species Abies spectabilis and Sorbus microphylla (not illustrated) which both occur in the closed forest and sparsely as krummholz above treeline, however here not in tree form as defined by Körner Speed et al, 2015;Zimmermann et al, 2010), whereas soil N concentrations (Of, Ah) significantly decrease ( Figure 6). Thus, significantly increasing C/N ratios ( Figure 6, Table 3; cf.…”
Section: Hohnwaldsupporting
confidence: 79%
“…Soil C concentrations (Of, Ah) slightly decrease with elevation, however not significantly (see also Speed et al, 2015; Zimmermann et al, 2010), whereas soil N concentrations (Of, Ah) significantly decrease (Figure 6). Thus, significantly increasing C/N ratios (Figure 6, Table 3; cf.…”
Section: Resultsmentioning
confidence: 91%
“…Tundra vegetation dominated by native shrubs sequesters a significant amount of atmospheric carbon [64]. Previous studies have shown that climate warming causes changes of carbon stocks in the vegetation of alpine tundra [11,[65][66][67][68]. A previous study of this system found that there were no significant changes in vegetative structure [29], indicating that climate warming would have limited impacts on the carbon stocks in the alpine tundra of Changbai Mountains.…”
Section: Implications For Vegetation Carbon Stock In Alpine Tundramentioning
confidence: 98%
“…Global warming is most pronounced at high latitudes where temperatures over the last 30 years have risen by 0.6°C per decade, which is twice as fast as the global average (Bekryaev et al 2010;Core Writing Team RKP and LAM 2014). Since it is largely considered that high altitude and latitude treelines are controlled by summer temperatures (Holtmeier and Broll 2007;Gehrig-Fasel et al 2008;MacDonald et al 2008) and growing season parameters (Körner and Paulsen 2004;Körner 2008), the ongoing warming trend is expected to cause important vegetation shifts and lead to significant changes in species composition and biomass production (Walther et al 2002;Epstein et al 2004;Gonzalez et al 2010;Paulsen and Körner 2014;Speed et al 2015). Despite the fact that treeline advances in Polar regions are mostly limited by temperature, other factors (e.g.…”
Section: Introductionmentioning
confidence: 99%